A Comparative Study of Oxidation in the Preparation of Lacton and Bislacton Compounds and Biological Activity Study of Product Compounds - Marwan Mohammed Farhan (Journal of Global Pharma Technology, 2018)
The Oxidation of five Compound Pyrylium salts with Potassium Permanganate were carried out at different temperature (room temperature, 0c0, 50c0). The reaction proved to be Complex, giving rise to multiple products. However, several major products were isolated at different temperature and identified, unsaturated, five-member ring Lacton, Bislacton and other by-products like Benzoic acid and it is derivatives and diagnosing them Spectroscopically (I.R., 1H-N.M.R.) in addition to the quantitative analysis to its elements. Biological activity of the three types from product compounds was detected on nine pathogenic bacterial species E. coli, Shi. sonni, Ps. areguginos, K. pneumoniae St. pyogenes, St.  Pneumoniae, S. aeureus, Sal. Typhi, and P. morganella. It was found that the product compounds had a good effect to inhibit growth of some pathogenic bacterial species. The best effective concentration of the products compounds against the bacterial growth of most species was 8000 g /mL Also; the results showed that the best compound of three types in an inhibition process was Bislacton, whose prepared concentrations had large impact.